Magnetic properties and Mössbauer spectroscopy of Cu-Mn substituted BaFe12O19 hexaferrites. Issue 17 (1st December 2017) - Baykal, A.; Güngüneş, H.; Sözeri, H.; Amir, Md.; Auwal, I.; Asiri, S.; Shirsath, S.E.; Demir Korkmaz, A.
Abstract: In this study, bimetallic (Cu-Mn) substituted M-type Ba1-2x Mnx Cux Fe12 O19 (0.0 ≤ x ≤ 0.1) hexaferrites were fabricated via sol-gel auto-combustion route. The effect of bimetallic substitution on structure, morphology and magnetism of BaFe12 O19 was studied. Scanning Electron Microscopy confirm images reveal the nanosize of the prepared products with flake morphology. X-ray powder diffraction analysis confirmed their complete conversion to BaFe12 O19 hexagonal crystal phase. The results from the magnetic investigations conducted by Vibrating Sample Magnetometer (VSM) and 57 Fe Mössbauer suggested that the saturation magnetization ( M s ) and the coercive field of Ba1-2x Mnx Cux Fe12 O19 hexaferrites decrease as the concentration of Cu and Mn increases. The cation distribution calculation showed that the occupancy of Fe 3+ ions is increased at 12k and 2b sites with the increase in Cu and Mn substitution.